A Possible Role of Prolonged Whirling Episodes on Structural Plasticity of the Cortical Networks and Altered Vertigo Perception: The Cortex of Sufi Whirling Dervishes - Cakmak, Yusuf O.; Ekinci, Gazanfer; Heinecke, Armin; Çavdar, Safiye (Frontiers in Human Neuroscience, 2017)
Although minutes of a spinning episode may induce vertigo in the healthy human, as a result of a possible perceptional plasticity, Sufi Whirling Dervishes(SWDs) can spin continuously for an hour without a vertigo perception.This unique long- term vestibular system stimulation presents a potential human model to clarify the cortical networks underlying the resistance against vertigo. This study, therefore, aimed to investigate the potential structural cortical plasticity in SWDs. MRI of 10 SWDs and 10 controls were obtained, using a 3T scanner. Cortical thickness in the whole cortex was calculated. Results demonstrated significantly thinner cortical areas for SWD subjects compared with the control group in the hubs of the default mode network , as well as in the motion perception and discrimination areas including the right dorsolateral prefrontal cortex, the right lingual gyrus and the left V5/MT and the left fusiform gyrus. In conclusion, this is the first report that warrants the potential relationship of the motion/body perception related cortical networks and the prolonged term of whirling ability without vertigo or dizziness.